Measuring Opportunities and Challenges in Dispute Resolution of Fintech Sharia Business Through LAPS - Siti Nurhayati; Nurjamil Nurjamil; Muhammad Haris Fadhillah (Faculty of Law, Universitas Pattimura, 2022)
This research was conducted to outline the opportunities and challenges of resolving fintech business disputes through the Alternative Dispute Resolution Institute (LAPS) in Indonesia. The research method used in this research is a legal reasearch approach and qualitative approach that is to review primary and secondary data sources related to regulations on business dispute resolution in Indonesia. The results show that fintech plays a role in encouraging the economic development of the community, especially as an alternative to financing. LAPS serves as a solution to dispute resolution of business people in Indonesia this institution was chosen because it is more effective and efficient, the verdict is final and binding that is contrary to litigation lines that seem time-consuming and expensive costs. LAPS opportunities are very large for the rise of digital-based businesses and payments that still leave many legal problems while LAPS khsusus fintech is not yet available where LAPS provides services that are in line with digital business; the settlement is a win-win solution, which is in accordance with the character of the business world, which is obliged to manage risks, including reputational risk, operational risk and legal risk. While the challenges faced by LAPS in fintech include: Dualism alternative fintech dispute resolution can be through LAPS and can also through the Consumer Dispute Resolution Agency (BPSK); Limited Legal Infrastructure The number of fintech transactions that continue to increase in line with the potential for disputes that will occur; Availability of Mediators and Arbitrators of LAPS Financial Services Sector.